2021
DOI: 10.3390/pharmacy9030136
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Novel Clinical Decision Support Tool for Pharmacist-Led Antimicrobial Stewardship in Patients with Normal Procalcitonin

Abstract: In 2018, a clinical decision support (CDS) tool was implemented as part of a “daily checklist” for frontline pharmacists to review patients on antibiotics with procalcitonin (PCT) <0.25 mcg/L. This study used a retrospective cohort design to assess change in antibiotic use from pharmacist interventions after this PCT alert in patients on antibiotics for lower respiratory tract infections (LRTI). The secondary outcome was antibiotic days of therapy (DOT), with a subgroup analysis examining antibiotic use and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…A study in the United States showed that the use of procalcitonin levels to guide interventions by clinical pharmacists led to discontinuation of vancomycin therapy in patients with lower respiratory tract infections and normal procalcitonin levels. 53 Rapid identification of gram-positive bacteria through diagnostic systems like the VITEK-2 automated system, matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF MS), and rapid polymerase chain reaction (PCR) with real-time ASP interventions by a clinical pharmacist have been implemented successfully in the United States. 19,20,54,55 Identification of antimicrobial susceptibility using Verigene along with ASP guidance can improve time to initiation of appropriate antimicrobials as well as reduce mortality rates and 30-day readmission rates.…”
Section: Evidence On the Efficacy Of Pharmacist-driven Asps In Asiamentioning
confidence: 99%
“…A study in the United States showed that the use of procalcitonin levels to guide interventions by clinical pharmacists led to discontinuation of vancomycin therapy in patients with lower respiratory tract infections and normal procalcitonin levels. 53 Rapid identification of gram-positive bacteria through diagnostic systems like the VITEK-2 automated system, matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF MS), and rapid polymerase chain reaction (PCR) with real-time ASP interventions by a clinical pharmacist have been implemented successfully in the United States. 19,20,54,55 Identification of antimicrobial susceptibility using Verigene along with ASP guidance can improve time to initiation of appropriate antimicrobials as well as reduce mortality rates and 30-day readmission rates.…”
Section: Evidence On the Efficacy Of Pharmacist-driven Asps In Asiamentioning
confidence: 99%
“…They suggest that prospective review and feedback and pre-prescription restrictions are 2 of the most effective actions and as such will be reviewed first. 23 Table 1 [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] summarized the actions employed and outcomes.…”
Section: Intervention By Typementioning
confidence: 99%
“…In the patients for whom interventions were made, one of the significant results was the discontinuation of vancomycin use (85.3% intervention vs 27.4% no intervention, P = .016). 43 The guideline usage to limit anti-MRSA therapy is not limited to adults. Lanata and colleagues added specific indications for empiric vancomycin use, incorporated in the PICU order set, to already occurring prospective review and feedback for bacterial community acquired infections.…”
Section: Guideline/protocol Changementioning
confidence: 99%
See 2 more Smart Citations